2020
DOI: 10.1063/5.0013692
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of spin waves through a Néel domain wall

Abstract: Spin waves have the potential to be used as a next-generation platform for data transfer and processing as they can reach wavelengths in the nanometer range and frequencies in the terahertz range. To realize a spin-wave device, it is essential to be able to manipulate the amplitude as well as the phase of spin waves. Several theoretical and recent experimental works have also shown that the spin-wave phase can be manipulated by the transmission through a domain wall (DW). Here, we study propagation of spin wav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…A deep analysis of the process in the upper vertex DW when the SW is propagated helps to understand this effects: for the high transmission angle range, the SWs experiments a phase shift close to π/2 (marked in red in Fig. 3b), which is in agreement with some mechanical systems in resonance and previous recorded phase-shifts in Néel-type DWs [16].…”
Section: Propagation Of the Edge Spin Wavessupporting
confidence: 87%
“…A deep analysis of the process in the upper vertex DW when the SW is propagated helps to understand this effects: for the high transmission angle range, the SWs experiments a phase shift close to π/2 (marked in red in Fig. 3b), which is in agreement with some mechanical systems in resonance and previous recorded phase-shifts in Néel-type DWs [16].…”
Section: Propagation Of the Edge Spin Wavessupporting
confidence: 87%
“…The SWs propagation across a 180° Neel-type DW, instead, was investigated by O. Wojewoda et al [77] A symmetric 180° Neel DW with a circular Bloch line (vortex) in the middle was stabilized in a waveguide patterned in a Fe78Ni22 film grown on a Cu (001) single crystal substrate (Figure 14 (a)-(c)). In order to have a stable DW at remanence and allow SW propagation in DE configuration, the waveguide was prepared with the long axis perpendicular to the easy direction of the Fe78Ni22 film.…”
Section: Interaction and Manipulation Of Spin Wavesmentioning
confidence: 99%
“…It has been recently demonstrated that in this system, spin waves can propagate in favorable Damon-Eshbach mode with high group velocities reaching almost 6 km/s in orthogonally magnetised waveguides without the necessity of applying the external magnetic fields [199]. The magnetic anisotropy can also be used to stabilize various spin structures unachievable in common material systems, and these spin structures can be further used to control spin-wave propagation [200].…”
Section: F Spin-wave Propagation In Materials With Locally Controlled...mentioning
confidence: 98%